Allostery through DNA drives phenotype switching - Gabriel Rosenblum (Nature Portfolio, 2021)
Most insights on DNA-mediated allostery upon transcription factor (TF) binding were either based on artificial promoters or found to be short-ranged. Here authors use single-molecule FRET and cryo-EM to show that Bacillus subtilis bacteria utilize long-range allostery in a stochastic and reversible phenotype switch.